2023
DOI: 10.3390/ijms24021287
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-Signalling in Human Glaucoma Lamina Cribrosa Myofibroblasts

Abstract: Glaucoma is one of the most common causes of treatable visual impairment in the developed world, affecting approximately 64 million people worldwide, some of whom will be bilaterally blind from irreversible optic nerve damage. The optic nerve head is a key site of damage in glaucoma where there is fibrosis of the connective tissue in the lamina cribrosa (LC) extracellular matrix. As a ubiquitous second messenger, calcium (Ca2+) can interact with various cellular proteins to regulate multiple physiological proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 137 publications
0
3
0
Order By: Relevance
“…Myofibroblasts may originate from epithelial cells (via a process called EMT), endothelial cells (via EndMT), regular fibroblasts and other cells [ 34 , 35 ]. Myofibroblasts and corresponding biological processes such as EMT have been reported to play a role in the context of glaucoma, for instance in retinal pigment epithelial cells [ 36 ], lamina cribrosa cells [ 37 ] and trabecular meshwork cells [ 38 , 39 ]. In keeping with our results, Tenon’s ocular fibroblasts from glaucomatous patients were reported to show signs of a myofibroblast phenotype by determining differential expression of a predefined panel of 10 genes [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Myofibroblasts may originate from epithelial cells (via a process called EMT), endothelial cells (via EndMT), regular fibroblasts and other cells [ 34 , 35 ]. Myofibroblasts and corresponding biological processes such as EMT have been reported to play a role in the context of glaucoma, for instance in retinal pigment epithelial cells [ 36 ], lamina cribrosa cells [ 37 ] and trabecular meshwork cells [ 38 , 39 ]. In keeping with our results, Tenon’s ocular fibroblasts from glaucomatous patients were reported to show signs of a myofibroblast phenotype by determining differential expression of a predefined panel of 10 genes [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, Ca consumption reached the recommended level was associated with a decreased risk of glaucoma. Ca 2+ is a second messenger that interacts with various cellular proteins and regulates multiple physiological processes that contribute to diseases including cancer, fibrosis, and glaucoma [ 34 ]. The intracellular concentration of Ca 2+ is low with a high inwardly directed concentration [ 35 ], and there are various pathways of cellular Ca regulation both extracellularly and intracellularly [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Study demonstrated that Ca dysregulation results in the wild-type myocilin misfolding initially and may further contribute broadly to glaucoma-associated endoplasmic reticulum stress [ 44 ]. Therefore, we postulated that enough dietary Ca intake could supplement Ca loss in the cytoplasm after excessive Ca 2+ entered mitochondria during the progression of glaucoma to maintain Ca 2+ homeostasis in lamina cribrosa cells [ 34 ].…”
Section: Discussionmentioning
confidence: 99%